Faithful Dissenters? Feminist Ecclesiologies and Dissent - Watson, Natalie (Scottish journal of theology, 1998)
The title of this article contains a paradox which I have chosen deliberately and the meaning of which will become clear during the course of it. The topic is ‘Women in Dissent’. A number of meanings could be attributed to this title. It could either be understood as ‘Women in the dissenting or non-conformist tradition’ or it could mean ‘dissenting women’ which is the option I have chosen. I want to discuss whether or not feminism, or to be more precise, feminist theology, can be understood as a form of dissent or in what respects it differs from the forms of dissent that would normally be studied in the dissenting or non-conformist tradition.